The functional analysis of verbal behavior in Verbal Behavior (1957) by B. F. Skinner (Brazilian Journal of Behavioral and Cognitive Therapy, 2003)
Verbal Behavior(1957), by B. F. Skinner, provides an innovative analysis of verbal behavior. Thisarticle presents and demonstrates some of the concepts and processes included in this work on thefunctional analysis of verbal behavior, such as: the concept and kinds of verbal behavior within afunctional analysis and their organization, multiple causation, the role of the listener (audience),verbal thought, the verbal community, conscience, among others. Daily and literary verbalbehavior are used as examples. Some of the questions that have been researched in the area ofverbal behavior, as well as some of the specific difficulties of its study, are briefly mentioned anddiscussed.